Outcomes of Class II composite restorations placed by dental students: An observational study - Ghada L AlOtaibi; Rwan Aldakheel; Haifa Alhussein; Shahd Alrowili (Wolters Kluwer Medknow Publications, 2020)
Introduction: Main objectives of restoring the teeth is to remove the caries and replace the tooth structure to restore form and function. This radiographic study aimed to determine the defective Class II composite restorations in permanent teeth placed by the undergraduate dental students in a private dental school. Materials and Methods: A retrospective analysis of bitewing radiographs of Class II composite restorations placed by the clinical dental students of 2017-2018 year was assessed to determine the defective restorations. Bitewing radiographs were examined to record voids, open contact, residual caries, open margin, defective restoration, and acceptable composite Class II restorations. Results: A total of 1514 permanent teeth filled with composite Class II restorations were assessed using bitewing radiographs. Almost 935 teeth showed signs of failure of Class II restorations. Reasons for the failure of most of the Class II composite restoration were due overhang 197 (13.01%), followed by voids 184 (12.15%), open contact 167 (11%), poor contour 165 (10.88%), open margin 135 (8.91%), and residual caries 87 (5.75%). A significant difference between male and female students was observed with regard to voids (P = 0.026), overhang (P = 0.016), and open margins (P = 0.001) of the Class II composite restorations. Conclusion: Overhang was the most common, and residual caries was the least common defects observed in the bitewings. Male dental students placed higher defective composite Class II restorations compared to the female dental students.